A primer on arts integration : strategies, lessons, and collective wisdom of teacher leaders - Goering, Christian Z.; Pham, Hung K.; Hackett-Hill, Kathryn; French, Seth D. (Emerald Publishing Limited : IAP | Information Age Publishing, Inc., 2023)
"This edited collection provides middle and high school classroom teachers of English language arts, social studies, and other disciplines the inspiration and insight necessary to utilize an arts integration approach in their teaching. Whether you want your students to create documentaries, maps, mixed media, songs, quilts, dances, masks, or a remix of multiple art forms, the point of school can and should be more about how students create their own meaning in powerful ways and harness their creativity for social good. Arts integration is one approach demonstrated to be invaluable in these terms, moving teachers and students into a what can we create today? mindset sure to inject energy into classrooms, learning, and lives"--